A Poisson Quasi Suja Distribution - Ogunmola, Adeniyi Oyewole; Bamigbala, Olateju Alao (Darul Yasin Al Sys, 2025)
Two-parameter Poisson Quasi Suja distribution (PQSD) derived from the two-parameter quasi suja distribution is proposed for extremely positively count data. Its survival and hazard functions, first four raw moments’ measures were expressed. The variance, coefficient of variation, index of dispersion, skewness and kurtosis were also obtained. The impacts of each parameter in the new distribution were assessed.